Association between suicidal behavior and genes of serotonergic system confirmed in men with affective disorders - Pawlak, Joanna; Dmitrzak-Węglarz, Monika; Skibinska, Maria; Szczepankiewicz, Aleksandra; Leszczynska-Rodziewicz, Anna; Czerski, Piotr; Zaremba, Dorota; Hauser, Joanna; Maciukiewicz, Małgorzata (Journal of Medical Science, 2014)
Introduction. Suicidal behavior is a crucial clinical problem in many groups of psychiatric patients. It occurs most often in affective disorders, psychotic disorders, substance abuse/dependence and personality disorders. Although not all patients with these diagnoses present suicidal behavior, it is very important to find the most vulnerable subgroups. The extensive number of studies shows that suicidal behavior (completed and attempted suicide) is associated with changes in functioning of serotonergic system. Tryptophan hydroxylase (TPH) is rate-limiting enzyme in biosynthesis of serotonin. Serotonin transporter (5-HTT) is the main factor removing serotonin from the synaptic space. Genetic studies confirm that suicide behavior has a genetic component independently of major psychiatric disorders. Aim. The aim of this study is to look for association between selected candidate genes and suicidal behavior in affective disorders.Material and methods. In the study we included 597 patients meeting DSM-IV criteria for bipolar disorder or unipolar disorder and 563 healthy controls. Polymorphism of serotonin transporter gene 5-HTTLPR and single nucleotide polymorphisms – SNPs (rs1799913 and rs1800532) in tryptophan hydroxylase 1 (TPH1) gene were analyzed. We used in computation Statistica 8.0 package (STATSOFT, Poland) (tests: The two-tailed Pearson's chi-square (?2) test and Fisher's exact test).Results. Main positive findings are an association between TPH1 polymorphisms and bipolar disease type I (BPI) diagnosis in men and an association between TPH1 polymorphisms and suicidal attempts in male patients. In all group we did not find nor allelic neither genotypic associations of selected polymorphisms and diagnosis or suicide attempts. Conclusions. Our findings partially confirm that serotonergic system plays a role in affective disorder and suicidal behavior, but the association needs further investigation.